2022
DOI: 10.1002/ece3.9041
|View full text |Cite
|
Sign up to set email alerts
|

Condition dependence in biosynthesized chemical defenses of an aposematic and mimetic Heliconius butterfly

Abstract: Aposematic animals advertise their toxicity or unpalatability with bright warning coloration. However, acquiring and maintaining chemical defenses can be energetically costly, and consequent associations with other important traits could shape chemical defense evolution. Here, we have tested whether chemical defenses are involved in energetic trade‐offs with other traits, or whether the levels of chemical defenses are condition dependent, by studying associations between biosynthesized cyanogenic toxicity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 110 publications
1
2
0
Order By: Relevance
“…Our data demonstrate how strongly H. erato biosynthesize CG during adulthood to maintain their defences while also investing in the protection of their offspring, corroborating previous findings (Castro et al 2020; Mattila et al 2022). Considering that a Heliconius female lays ca.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our data demonstrate how strongly H. erato biosynthesize CG during adulthood to maintain their defences while also investing in the protection of their offspring, corroborating previous findings (Castro et al 2020; Mattila et al 2022). Considering that a Heliconius female lays ca.…”
Section: Discussionsupporting
confidence: 92%
“…Mattila et al (2022) demonstrated that Heliconius butterflies keep their CG concentration at high levels during adulthood until their natural death. Indeed, if these aposematic butterflies lost their toxicity as they age, this would dilute the protection signal of their colour pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation